Using Poison Center Data for Postdisaster Surveillance. Issue 5 (10th September 2014) - Wolkin, Amy; Schnall, Amy H.; Law, Royal; Schier, Joshua
Abstract: The role of public health surveillance in disaster response continues to expand as timely, accurate information is needed to mitigate the impact of disasters. Health surveillance after a disaster involves the rapid assessment of the distribution and determinants of disaster-related deaths, illnesses, and injuries in the affected population. Public health disaster surveillance is one mechanism that can provide information to identify health problems faced by the affected population, establish priorities for decision makers, and target interventions to meet specific needs. Public health surveillance traditionally relies on a wide variety of data sources and methods. Poison center (PC) data can serve as data sources of chemical exposures and poisonings during a disaster. In the US, a system of 57 regional PCs serves the entire population. Poison centers respond to poison-related questions from the public, health care professionals, and public health agencies. The Centers for Disease Control and Prevention (CDC) uses PC data during disasters for surveillance of disaster-related toxic exposures and associated illnesses to enhance situational awareness during disaster response and recovery. Poison center data can also be leveraged during a disaster by local and state public health to supplement existing surveillance systems. Augmenting traditional surveillance data (ie, emergency room visits and death records) with other data sources, such as PCs, allows for better characterization of disaster-related morbidity and mortality. Poison center data can be used during a disaster to detect outbreaks, monitor trends, track particular exposures, and characterize the epidemiology of the event. This timely and accurate information can be used to inform public health decision making during a disaster and mitigate future disaster-related morbidity and mortality. A Wolkin, AH Schnall, R Law, J Schier .Using poison center data for postdisaster surveillance .Prehosp Disaster Med .2014 ;29 (5 ):1 -4 .